Customer Purchase Patterns and Loyalty in MSME Catering Businesses Using the RFM Method - Suzyanty Mohd Shokory; Nadratun Nafisah Abdul Wahab; Jihan Zanubiya; Zuraidah Zainol (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2026)
The increasing competition in the catering industry necessitates a data-driven understanding of consumer behavior to support effective customer retention strategies. This study aims to identify customer purchase patterns and loyalty in MSME Catering using the RFM (Recency, Frequency, Monetary) method based on transaction data from January 2025 to May 2026. This research addresses a gap in the literature regarding the application of transaction-based analytics for customer loyalty in MSMEs, which previously relied more on surveys or subjective perceptions. A total of 564 transactions from 80 unique customers were analyzed quantitatively, processed using Google Sheets, and visualized with Tableau. The results indicate that 55 customers (68.75%) are classified as loyal, while 25 customers (31.25%) are new customers. RFM segmentation grouped customers into Champions, Loyal Customers, Potential Loyalist, Need Attention, and Lost Customers, with the majority in the Potential Loyalist, Need Attention, and Lost segments. In addition to descriptive statistics, the relationship between purchase frequency and monetary value was examined to provide deeper insights into customer behavior. The findings demonstrate that the RFM approach provides a structured understanding of customer loyalty and transaction value, supporting the development of targeted marketing strategies, including loyalty programs, reminder promotions, reactivation campaigns, and customer engagement initiatives. This study contributes a practical RFM-based analytical framework applicable to MSMEs to enhance retention and marketing effectiveness.